LEARNING OF CYBER-LITERATURE BASED ON LOCAL WISDOM IN CREADING CHARACTERISTICS OF STUDENTS IN HAVING THE SOCIETY 5.0 ERA - Hennilawati Hennilawati; Sri Kurnia Hastuti Sebayang; Toras Barita Bayo Angin (IKIP Siliwangi, 2022)
The reducing of local wisdom value in industrial revolution has been marked with increasing of digitalization activities on human life, in which it is one be worried to affect pola of life characteristics of young generation. The Society 5.0. era can be known with critical-mindset in getting adaptation for the future, such as: analytical, critical, and creativity. Then the qualitative method is used to conduct this research with documentation through literature review and interview as the techniques for collecting data. The cyber-literature based on local wisdom in creating characteristics of the students on society 5.0. should be filled into three abilities, namely: basic-literature, skill, and character. The learning of cyber-literature based on local wisdom in creating characteristics of the students should be taken into effectively, contextual, and innovative, in which they are functioned to create the motivation as well as interest of the students in reading local-literature by looking the aspects of kindness-values that worked to create the characteristics of the students in the brilliant-future. Keywords: Cyber-Literature, Local Wisdom, Characteristics of Society 5.0.